Successful Tulasnella amonilioides isolation from wild Cattleya intermedia and effectiveness of the mycobiont on in vitro propagation of this threatened Orchidaceae - Endres Júnior, Delio; Alves-Silva, Genivaldo; Sasamori, Márcio Hisayuki; Silveira, Rosa Mara Borges da; Droste, Annette (Journal of Environmental Analysis and Progress, 2023)
This is the first study that reports symbiosis in Cattleya, aiming to isolate and identify mycorrhizal fungi capable of promoting the germination of this orchid and to evaluate the development of symbiotically propagated individuals. We compared seed germination percentage, growth index, and morphometric variables of seedlings propagated symbiotically in oatmeal agar (OMA) medium with individuals that were non-symbiotically propagated in Murashige and Skoog (MS) medium. Fungi isolates were identified by phylogenetic analysis and eight of the nine isolates that were efficient in C. intermedia propagation were identified as Tulasnella amonilioides. The mycobiont improved C. intermedia seed germination and plant development when compared with OMA medium without fungi (negative control). Seedlings propagated by symbiotic culture with T. amonilioides produced more leaves and longer roots, while shoot height and a number of roots were lower than for seedlings propagated in MS medium with the addition of activated charcoal. The fresh mass of seedlings propagated by symbiotic and a symbiotic techniques was equal, except when seedlings were grown in MS without activated charcoal. T. amonilioides enhance the in vitro propagation of C. intermedia and provide plants that facilitate symbiotic processes in reintroduction environments.